2015
DOI: 10.46568/pjass.v2i1.283
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ Awareness And Experiences Of Having A Thalassemic Child: A Qualitative Approach

Abstract: The purpose of this study is to understand the mothers’ level of awareness regarding thalassemia and their experiences of having a thalassemic child. A total of (N=64) mothers are chosen as participants. Focus Group Discussion (FGD) is carried out. Majority of the children’s parents is cousins but they are not screened for thalassemia before marriage and despite of the birth of thalassemic child, they are unaware about pre-natal diagnosis. The study highlights the need of implementing effective public educatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 13 publications
1
9
1
Order By: Relevance
“…Parents’ major worries are divided into the following levels: family level which includes child care and communication between healthy and sick children; society level which includes development of patients in the society and their new educational lives. 27 In a study, thalassemia is introduced as a life-threatening disease affecting family members and their activities, thus affecting the management of life and children. Furthermore, thalassemia imposes stresses on the quality of life and health of children and parents because of its severity, treatment burden and long care process, and high levels of parental responsibilities toward children in society and their evolution process.…”
Section: Discussionmentioning
confidence: 99%
“…Parents’ major worries are divided into the following levels: family level which includes child care and communication between healthy and sick children; society level which includes development of patients in the society and their new educational lives. 27 In a study, thalassemia is introduced as a life-threatening disease affecting family members and their activities, thus affecting the management of life and children. Furthermore, thalassemia imposes stresses on the quality of life and health of children and parents because of its severity, treatment burden and long care process, and high levels of parental responsibilities toward children in society and their evolution process.…”
Section: Discussionmentioning
confidence: 99%
“…In Pakistan over 5000 children with thalassemia major are born every year. Pakistan carries a risk of 6% of the population as heterozygous carriers serving as potential source of spread of thalassemia major 6…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that some parents of thalassemia patients are not aware of their carrier status prior to marriage [ 4 ]. In addition, it was found that married couples often had inadequate knowledge related to the genetic nature of thalassemia and did not undergo pre-marital screening [ 23 ].…”
Section: Discussionmentioning
confidence: 99%